WILL THE "TRUE" LABOR SHARE STAND UP? AN APPLIED SURVEY ON LABOR SHARE MEASURES. (7th March 2018) - Mućk, Jakub; McAdam, Peter; Growiec, Jakub
Abstract: Labor's share of income is a key variable in economics. It plays a leading role in analysis of (in)equality, globalization, technical change, growth theories, etc. Notwithstanding this broad application, there are many different definitions of the labor share. Understanding and synthesizing those differences is the purpose of this applied survey. Empirical measures may vary reflecting the allocation of income components that cannot be directly ascribed to capital or labor. We examine the alternative assumptions made in the literature in this regard and quantify and motivate the resulting discrepancies. Focusing (mostly) on US data, we show that different measures can have very distinct properties in terms of the observed stochastic trends, shares of short‐, medium‐, and long‐run variation and volatilities, persistence and mean‐reversion properties, and susceptibility to structural breaks. For instance, while "short‐run" properties of the surveyed labor share measures are relatively consistent across all definitions (and countercyclical), their "medium‐" and "long‐run" trends may diverge substantially (and are procyclical). To substantiate our analysis, we document the implications of discrepancies in the empirical labor share definition for growth accounting, analyzing the effect of technology shocks, and for estimating inflation dynamics.